Hand crossing of cowpeas - Myers, G.O. (1996)
In genetic improvement of cowpea, one plant or variety rarely has every desirable characteristic. The recombination of desirable characteristics from different parental sources is achieved by crossing plants and the necessary cross pollinations. This document presents a method for the cross pollination of cowpea developed at UTA.